Pharmacists at the frontline beating the COVID-19 pandemic - Nadia Bukhari; Huma Rasheed; Bismah Nayyer; Zaheer- (Taylor & Francis Group, 2020)
As the lockdowns are being observed all over the globe and the national level pharmacy professionals are performing frontline roles, this editorial highlights the role of pharmacists in the COVID − 19 pandemic. Pharmacists globally are providing services amidst pandemic, including TRIAGE services, seeing patients and reducing the patients' burden on health care facilities such as hospitals and GP practices. Pharmacists are also working to providing home deliveries, as well as dealing with the increasing number of patients coming through to pharmacies with the other ailments. Pharmacy associations have issued their guidelines and in this editorial, several global examples of pharmacists' role in the COVID 19 are being discussed. Pakistan is used as a country case study in this editorial. The editorial also elaborates how pharmacists in the UK and Pakistan have teamed up together to compile 10-steps protection guidelines for the pharmacy teams in Pakistan in English and Urdu language. This 10-point guidance educates community pharmacies for safety and standard operation as the number of patients in the country continues to rise. These guidelines are endorsed by the government and private bodies. These can be adopted and adapted by any country; keeping in view their laws and regulations.